Pattern of corticosteroid allergy in Thailand - Penpun Wattanakrai (2018)
Background: Corticosteroid allergy is a complication of topical therapy detected by patch-testing with corticosteroid allergens. Objective and Methods: Ten-year retrospective review to study the prevalence and patterns of corticosteroid allergy in Thai patients. Results: Of 882 patients who were patch-tested, 29 (3.29%) had allergic reactions to corticosteroids. Of these 29 patients, 17 (58.62%) had positive reactions to one corticosteroid, and 12 (41.38%) reacted to multiple corticosteroids. Rates of reaction to corticosteroid groups ranged from 31.03 to 80.95%. Concomitant reactions between groups were noted. The prevalence of topical corticosteroid allergy (using two screening allergens, tixocortol pivalate and budesonide) was 2.27% (20 of 882). Testing with additional steroid allergens in suspected cases increased the prevalence to 3.29%. Tixocortol pivalate detected 51.72% of corticosteroid- allergic cases, and budesonide detected 24.14%. Combining both tixocortol and budesonide detected 68.97% of cases. Conclusion: Corticosteroid allergy is found to multiple corticosteroids, and concomitant reactions occur across groups. Group D1 corticosteroid esters produced a higher positive reaction rate (61.9%) than groups D2 (52.38%) and A (51.72%). This may be due to different prescribing habits or the easy access to D1 corticosteroids sold over the counter by pharmacies in Thailand. © 2010 American Contact Dermatitis Society. All Rights Reserved.